2015
DOI: 10.1016/j.aorn.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

ECG Interpretation Using the CRISP Method: A Guide for Nurses

Abstract: Nurses often struggle with identifying electrocardiogram (ECG) rhythms, but rapidly interpreting these rhythms is an essential skill that every nurse should master, especially in the perioperative setting. The CRISP (Cardiac Rhythm Identification for Simple People) method is an algorithm designed to help nurses rapidly interpret ECGs. Key aspects of assisting patients with suspected cardiac issues include the nursing assessment, correct three-lead ECG placement, and calculation of the heart rate. Then the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…For study I, heart rate data was collected from the open source cyton board plus ECG and the ADI ECG. In concordance with ECG recordings, the latter device was set-up to create three axes triangulating the heart [33]. The electrodes from both devices were placed using the standard three-lead placement: 1) inferior to the right clavicle, 2) interior to the left clavicle, and 3) superior and laterally to the right of the umbilicus [33].…”
Section: Instrumentationmentioning
confidence: 99%
“…For study I, heart rate data was collected from the open source cyton board plus ECG and the ADI ECG. In concordance with ECG recordings, the latter device was set-up to create three axes triangulating the heart [33]. The electrodes from both devices were placed using the standard three-lead placement: 1) inferior to the right clavicle, 2) interior to the left clavicle, and 3) superior and laterally to the right of the umbilicus [33].…”
Section: Instrumentationmentioning
confidence: 99%
“…The CRISP method is an algorithm designed to enable nurses to interpret ECGs rapidly [ 15 ]. Compared with traditional ECG analysis methods, it only takes three steps to identify the cardiac rhythm, then provides sufficient information for the risk stratification of arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…This method can therefore yield a significant improvement in nurses’ ECG learning [ 12 ]. The CRISP (Cardiac Rhythm Identification for Simple People) method is an innovative algorithm designed to help nurses rapidly interpret ECGs [ 15 , 16 ]. It has been shown that the CRISP method for interpreting primary cardiac arrhythmia by nurses is effective, simple, easy.…”
Section: Introductionmentioning
confidence: 99%
“…4 Every nurse should be able to recognise basic ECG rhythms, such as normal sinus rhythm, sinus tachycardia, sinus bradycardia, atrial fibrillation, atrial flutter, heart blocks, ventricular fibrillation and asystole. 5 It is required that the nurse must be responsible for monitoring and making clinical decisions based on information obtained from the monitor.…”
Section: Introductionmentioning
confidence: 99%
“…9 Many methods had been designed like CRISP (Cardiac Rhythm Identification for Simple People) which helps nurses to rapidly interpret ECG. 5 Also American Heart Association designed a PULSE trial (Practical Use of the Latest Standards for Electrocardiography trial) which is an online ECG monitoring education programme and strategies to implement and sustain change in practice, led by nurse champions on each unit and this trial increases nurses' knowledge of ECG monitoring, quality of care related to ECG monitoring and the patient outcomes.…”
mentioning
confidence: 99%